Analyzing the Relationship of English Language Learning Anxiety and English Language Learning Strategy Use Among English Major Undergraduates in Shi Jiazhuang, China - Fei, Wang (JOURNAL OF ADVANCES IN LINGUISTICS, 2019)
The study investigated the general state of foreign language learning anxiety and the relationship between foreign language learning anxiety and foreign language learning strategy among English major college students in Shi Jiazhuang, China. The quantitative research method was adopted in this study. The instruments were Foreign Language Class Anxiety Scale and Strategy Inventory Language Learning. The subjects were 400 English major students from Shi Jiazhuang College. The results showed that there exists a negative relationship between foreign language learning anxiety and the use of foreign language learning strategy. According to the findings of this study, it is necessary to reduce learners’ foreign language learning anxiety so as to apply more types of foreign language learning strategies efficiently, especially for those foreign language learners with high-level learning anxiety. Some suggestions were put forward for pedagogical implications, which will make Chinese learners be more successful during the process for foreign language acquisition.